2016
DOI: 10.1142/s0219455415500583
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Body Dynamic Model for Analysis of Localized Track Responses in Vicinity of Rail Discontinuities

Abstract: Rail discontinuities are one of the main sources of wheel impact causing high levels of noise, vibration and stresses in railway track. Even though various multi-body train-track interaction models have been developed in the past decade, accurate modeling and analysis of the track dynamic behavior in the vicinity of rail discontinuities is rare in the literature. In this paper, formulation of a new explicit multi-body dynamic (MBD) model incorporating detailed wagon, wheel-rail subsystems and track containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Each wheel was characterized by a mass of . The mass matrix ([ ]), the damping matrix ([ ]) and the stiffness matrix ([ ]) of vehicle were defined by equations (2) to (4), respectively (Askarinejad and Dhanasekar 2016, Khajehdezfuly 2019, Mosayebi et al 2017, Sadeghi et al 2016b, 2019…”
Section: Development Of Vehicle-track Modelmentioning
confidence: 99%
“…Each wheel was characterized by a mass of . The mass matrix ([ ]), the damping matrix ([ ]) and the stiffness matrix ([ ]) of vehicle were defined by equations (2) to (4), respectively (Askarinejad and Dhanasekar 2016, Khajehdezfuly 2019, Mosayebi et al 2017, Sadeghi et al 2016b, 2019…”
Section: Development Of Vehicle-track Modelmentioning
confidence: 99%
“…In order to run a dynamic nonlinear analysis and get accurate results, it is recommended to use proper hyper-elastic and hysteresis data in accordance with the viscoelastic properties of the USP Rubber [11]. On the contrary, Witt [8] evaluated the effects of USPs in railway track dynamics, and the USPs were modelled as elastic isotropic material [1]. Three types of stiffness were used in this study which the details are shown in Table II.…”
Section: Materials Model For Uspsmentioning
confidence: 99%
“…Stiffness for Different Cases of Support ConditionIn another study done by Dahlberg[7], it was recommended to use a vertical stiffness of 13 MN/m 2 for soft ballast beds and 26 MN/m 2 for stiff ballast beds. Askarinejad & Dhanasekar[8] used 15MN/m 2 uniform vertical stiffness. Whereas Witt[8] modelled the ballast bed as elastic isotropic material and the soft part of ballast was modelled with a 30 MPa Young Modulus and 20 kN/mm vertical stiffness and for the stiff ballast, 110 MPa Young Modulus and 60 KN/mm…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…See for instance, Handoko and Dhanasekar [20] pointed out that the traction and braking forces are seldom considered in the practice of wagon dynamics simulation, although these forces will greatly modify the wheel-rail contact parameters and then the wheelset dynamics; Liu et al [21] also studied the mechanism of wheelset longitudinal vibration by analysing the process of wheel/rail rolling contact; generally, the track defects can cause profound effects to the dynamics of the railway wagon; Zhang and Dhanasekar [22] noticed this problem and published a model for the dynamics of wagons subject to braking/traction torques on a perfect track by explicitly considering the pitch degree of freedom for wheelsets [23,24] and extended this model for cases of lateral and vertical track geometry defects and worn railhead and wheel profiles; Grossoni et al [25] examined the dynamic behaviour at a rail joint using a two-dimensional vehicle-track coupling model, where the influence of the number of layers and the number of elements between two sleepers and the beam model are investigated. Laterally, Zong and Dhanasekar [26] considered the gap between rail joints to account for thermal movement and to maintain electrical insulation for the control of signals and/or broken rail detection circuits; besides, railhead can provide high stresses due to the passage of heavily loaded wheels through a very small contact patch [27], and a multibody dynamic model was developed in [28] to accurately model and analyse the track dynamic behaviour in vicinity of rail discontinuities; recently Zong and Dhanasekar [29] provided a idea of simplifying the design of the IRJs consisting of only two pieces of insulated rails embedded into a concrete sleeper; Ling et al [30] presented a formulation for a passive roadrail crossing involving stiffened edges of the raised road pavement to minimise the risk of failure of wheel-rail contact using a nonlinear three-dimensional multibody dynamics model; additionally, a series of work on impact derailment due to lateral collisions between heavy road vehicles and passenger trains at level crossings and the associated derailments had also been conducted in [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%